2016
DOI: 10.4338/aci-2015-12-ra-0183
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and validation of a search algorithm to retrospectively identify CRRT initiation in the ECMO patients

Abstract: The use of an electronic search strategy resulted in determining an accurate CRRT initiation time among ECMO patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The results of this study are in line with other published studies emphasizing the bene t of electronic search strategies in big dataset extraction. [29,40] Strengths: This method of electronic data extraction by automated algorithm through institutional software connected to EHR is cost-effective, fast, and accurate compared to manual chart review. The total time frame for the physician researcher JS to conduct manual chart reviews of each set of 100 patients was about 15 hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study are in line with other published studies emphasizing the bene t of electronic search strategies in big dataset extraction. [29,40] Strengths: This method of electronic data extraction by automated algorithm through institutional software connected to EHR is cost-effective, fast, and accurate compared to manual chart review. The total time frame for the physician researcher JS to conduct manual chart reviews of each set of 100 patients was about 15 hours.…”
Section: Discussionmentioning
confidence: 99%
“…The adoption of electronic health records (EHR) in place of traditional paper charts has provided unprecedented amounts of information (Big data) that allows researchers to evaluate larger cohorts of patients than traditional research approaches. [28,29] Harnessing the potential of the EHR and the vast amounts of data within is challenging but developing and applying automated search strategies is a helpful approach. By using these tools to identify when an interpreter is utilized we can support quality improvement initiatives, enhance clinical practice, and improve our research accuracy and e ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal membrane oxygenation (ECMO), as a mechanical circulatory support system, is utilized as a treatment for cardiovascular or respiratory failure [1,2,3]. There are two main types of ECMO, including venovenous (VV)-ECMO for patients with isolated respiratory failure and venoarterial (VA)-ECMO for combined severe cardiac and respiratory failure [4].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated an automated search strategy for ARDS that could effectively and accurately identify patients based on the accepted clinical definition (i.e., Berlin definition, among ICU patients). Several previously automated search strategies have been described in the literature ( 13 15 , 21 , 22 ); however, to date, the Berlin definition has not been used as a digital signature of ARDS patients.…”
Section: Discussionmentioning
confidence: 99%